2021
DOI: 10.3390/ani11092557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNAs in the Anterior Pituitary in Rats Treated with GnRH

Abstract: The pituitary gland, an important endocrine organ, can secrete a variety of reproductive hormones under the action of hypothalamus-secreted gonadotropin-releasing hormone (GnRH) and plays important roles in animal reproduction. Circular RNAs (circRNAs) are a class of RNA molecules with stable covalently closed circular structures. CircRNAs are equipped with miRNA response elements (MREs), which can regulate the expression of target genes by competitively binding miRNAs. However, whether the expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 78 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Our previous research revealed significant differences in methylation levels in the adenohypophyses of rats after GnRH treatment [ 24 ]. In addition, 14 circRNAs were found to be significantly differentially expressed in the rat adenohypophysis [ 22 ]. However, the overall regulatory effects of GnRH on the expression of other ncRNAs and mRNAs in the rat adenohypophysis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research revealed significant differences in methylation levels in the adenohypophyses of rats after GnRH treatment [ 24 ]. In addition, 14 circRNAs were found to be significantly differentially expressed in the rat adenohypophysis [ 22 ]. However, the overall regulatory effects of GnRH on the expression of other ncRNAs and mRNAs in the rat adenohypophysis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The animals used in the experiments were 8-week-old male Sprague Dawley (SD) rats, provided by the laboratory Animal Center of Jilin University. The grouping strategy used for this study has been described previously [ 22 ]. Briefly, 12 SD rats were equally divided into four groups: two control groups and two experimental groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Circ-ZNF609 regulates nasopharyngeal carcinoma cell growth via modulating miR-188 expression [50]. Some studies have identified circRNAs in the pituitary gland [51][52][53][54]. At present, there have been few reports of circRNA regulating GH.…”
Section: Discussionmentioning
confidence: 99%